A pulse amplitude modulation scheme based on in-line semiconductor optical amplifiers (SOAs) for optical soliton systems - Aadel M. Alatwi; Ahmed Nabih Zaki Rashed (Institute of Advanced Engineering and Science, 2021)
The objective of this work is to simulate a pulse amplitude modulation (PAM) scheme based on in-line semiconductor optical amplifiers for optical soliton systems. The max. power for soliton systems, based on various bits/symbol PAM modulation schemes after a fiber length of 100 km, is simulated and clarified. In addition to the max. Q factor for soliton systems, PAM modulation schemes with various in-line SOA injection currents and a fiber length of 100 km are also simulated and demonstrated in the results. The total electrical power after photo-detectors for soliton systems, based on PAM modulation schemes with various in-line SOA injection currents and a fiber length of 100 km, is also simulated and clarified in the results. The study emphasizes that the higher the SOA injection current, the higher the electrical power and the lower the Q factor that can be achieved in the soliton system.